IMPACT OF TECHNOLOGY ON MODERN EDUCATION - Khudoyberdiyeva Odina Marubjan’s daughter (Galaxy International Interdisciplinary Research Journal, 2024)
This article investigates the profound impact of technology on modern education, analyzing how digital tools and innovations are reshaping teaching methodologies, learning experiences, and student outcomes. It explores the role of technology in enhancing accessibility, personalizing learning, and fostering engagement, while also addressing challenges such as the digital divide and the risk of over-reliance on technology. Through a comprehensive literature review and case studies, the research highlights both the benefits and the challenges of integrating technology into education, offering insights into the future of digital learning.